Adjusting to living with Parkinson's disease; a meta-ethnography of qualitative research. Issue 23 (6th November 2022) - Wieringa, Gina; Dale, Maria; Eccles, Fiona J. R.
Abstract: Purpose: Parkinson's disease (PD) is a condition which causes significant difficulties in physical, cognitive and psychological domains. It is a progressive condition which people have to live with for a long time; consequently, there is a need to understand what contributes to individual adjustment. This review aimed to answer the question "how do individuals adjust to PD?" Method: A systematic search of three databases (MEDLINE, CINAHL and PsycINFO) was carried out of papers documenting the adjustment process when living with PD and the findings were synthesised using a meta-ethnographic approach. Results: After exclusion based on eligibility criteria, 21 articles were included and were assessed for quality prior to analysing the data. Three main themes are proposed relating to the process of adjustment: "maintaining a coherent sense of self", "feeling in control" and "holding a positive mindset". Although many of the studies described challenges of living with PD, the results are dominated by the determination of individuals to self-manage their condition and maintain positive wellbeing. Conclusion: The results highlight the need to empower patients to self-manage their illness, mitigating the effects of Parkinson's disease and supporting future wellbeing. IMPLICATIONS FOR REHABILITATION: Individual identity disruption impacts on the self-value and sense of self coherence in individuals living with Parkinson's disease. Healthcare professionals should appreciate the complexity of the adjustment process which is related to the ability to maintain a coherent sense of self, to feel in control and to hold a positive mindset. Healthcare professionals should ensure information and knowledge related to self-management is tailored to an individual's understanding and experience of the disease.